A more sustainable urban future calls for action: the city of Lahti as European Green Capital 2021. Issue 1 (12th September 2021) - MacGregor-Fors, Ian; García-Arroyo, Michelle; Kotze, D Johan; Ojala, Elina; Setälä, Heikki; Vauramo, Saara
Abstract: In 2020, a small urban center from southern Finland, the City of Lahti, was awarded the 2021 European Green Capital, which recognizes and rewards local efforts that seek to improve the urban environment, together with its economy and the quality of life for its inhabitants, further posing ambitious goals for ecological improvement. In this commentary, we describe some of the key elements that made Lahti the 2021 European Green Capital, as well as some of the future plans for the city. We also highlight the importance of research-based knowledge as the foundation for achieving better outcomes in urban decision making.